2017
DOI: 10.4236/jss.2017.56017
|View full text |Cite
|
Sign up to set email alerts
|

The Psychological Well-Being among Left-Behind Children of Labor Migrant Parents in Rural Northern Vietnam

Abstract: Background: In Asia, especially in China and ASEAN, it has been an obvious trend that the population in general and parents in particular leave the countryside to bigger cities or more developed countries for employment opportunities. Many migrant workers are forced to leave their children at home with caregivers, particularly in families with both husband and wife working away from home. Studies worldwide have showed that, besides positive economic and social impacts, labor migrant parents also cause negative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 14 publications
(19 reference statements)
1
11
0
Order By: Relevance
“…Overall, the mental health outcomes of the rural children in the current study were poor when compared to their peers in other studies that also use the SDQ. The average SDQ total difficulties score in our study (12.93) is higher than those reported by studies conducted in developed countries [ 51 , 52 , 53 , 54 ] and similar to those reported by studies conducted in rural areas of other developing countries [ 55 , 56 ]. Compared to total difficulties scores reported in other studies of children in China, the mean score in our study is also among the highest [ 42 , 57 ].…”
Section: Discussionsupporting
confidence: 85%
“…Overall, the mental health outcomes of the rural children in the current study were poor when compared to their peers in other studies that also use the SDQ. The average SDQ total difficulties score in our study (12.93) is higher than those reported by studies conducted in developed countries [ 51 , 52 , 53 , 54 ] and similar to those reported by studies conducted in rural areas of other developing countries [ 55 , 56 ]. Compared to total difficulties scores reported in other studies of children in China, the mean score in our study is also among the highest [ 42 , 57 ].…”
Section: Discussionsupporting
confidence: 85%
“…Studies on LBC in Vietnam have mentioned various aspects such as nutrition, perception (Nguyen, 2016), behaviour problems (Nguyen, 2017), subjective wellbeing (Graham & Jordan, 2011;Nguyen et al, 2018) and self-esteem (Giang et al, 2019). However, there is little research on current situation and factors affecting loneliness in LBC in Vietnam.…”
Section: Present Studymentioning
confidence: 99%
“…Studies worldwide have shown that, besides positive economic impacts or increased household incomes through remittances that also support LBC's education [10][11][12], parental migration negatively influences the lives of children left behind [4,12,13]. Left-behind children, especially those with both parents migrating, are reported to have higher emotional problems and are more likely to experience poor psychological wellbeing compared to their counterparts [14][15][16][17][18]. Studies in Asian countries such as China, Vietnam, Nepal, Thailand, and the Philippines, have reported that compared to children with non-migrating parents, LBC have higher levels of depression, anxiety, loneliness, and lower levels of self-esteem, and have been reported to experience reduced happiness [12,15,[17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%